2010
DOI: 10.4103/0970-1591.65386
|View full text |Cite
|
Sign up to set email alerts
|

Cost benefits of intraoperative cell salvage in radical cystectomy

Abstract: Objective:We have looked into the clinical and financial benefits of using intra-operative cell salvage (ICS) as a method to reduce the amount of autologous blood transfusion (ABT) requirement for our radical cystectomy (RC) patients.Materials and Methods:Fifteen consecutive patients undergoing radical cystectomy received cell salvaged blood (ICS), while 15 did not (NCS). The cost of using the cell saver, number of homologous transfusions, survival, and recurrences were recorded and compared using paired t-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 19 publications
4
23
1
Order By: Relevance
“…In the setting of RC or PN, complication rates for groups receiving ICS or no blood conservation technique were 39.5% vs 40.5% and 21% vs 17% , respectively. Lastly, Ubee et al reported non‐cancer‐related post‐cystectomy peri‐operative mortality in both ICS (one death) and no blood conservation technique groups (two deaths).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the setting of RC or PN, complication rates for groups receiving ICS or no blood conservation technique were 39.5% vs 40.5% and 21% vs 17% , respectively. Lastly, Ubee et al reported non‐cancer‐related post‐cystectomy peri‐operative mortality in both ICS (one death) and no blood conservation technique groups (two deaths).…”
Section: Resultsmentioning
confidence: 99%
“…All were observational studies, representing low‐level evidence. Eligible publications assessed patients undergoing open RRP (11 studies ), open RC (two studies ) and open PN (one study ). There were no studies on ICS during urological laparoscopic or robot‐assisted procedures, nor for other major urological procedures associated with high peri‐operative transfusion rates, such as retroperitoneal lymph node dissection.…”
Section: Resultsmentioning
confidence: 99%
“…7 There is evidence to suggest that it is cost-effective, safe and may reduce the need for blood transfusion in both radical prostatectomy and radical cystectomy; however, many cystectomy patients are ineligible due to preoperative anemia. 7,15,16 Autologous blood banking involves blood donation prior to surgery, but is time consuming, inconvenient to the patient, and has a high discard rate. 16,17 Lastly, autologous blood recovery (CellSaver) is the reinfusion of blood lost during the operation, which is collected, filtered, washed, processed and re-transfused, but is controversial among urologists due to theoretical risks of cancer dissemination.…”
Section: Acute Normovolemic Hemodilutionmentioning
confidence: 99%
“…7,15,16 Autologous blood banking involves blood donation prior to surgery, but is time consuming, inconvenient to the patient, and has a high discard rate. 16,17 Lastly, autologous blood recovery (CellSaver) is the reinfusion of blood lost during the operation, which is collected, filtered, washed, processed and re-transfused, but is controversial among urologists due to theoretical risks of cancer dissemination. 16,18 Interestingly, experienced urologists use these techniques more commonly than less experienced surgeons.…”
Section: Acute Normovolemic Hemodilutionmentioning
confidence: 99%
See 1 more Smart Citation